Systematic Literature Review: The Influence of Learning Media on Student Learning Outcomes on Solar System Material - Nuha Febry Anisa; Panjaitan, Aries Dame Uli; Tanjung, Yul Ifda; Fairuz, Tariza (UNIVERSITAS NEGERI MEDAN, 2025)
Learning about the solar system at the junior high school level poses challenges due to its abstract nature, making conventional methods less effective. This study aims to analyze the effect of learning media on junior high school students' learning outcomes on solar system material using the Systematic Literature Review (SLR) method. Research data were collected through Google Scholar using the PRISMA (Preferred Reporting Items for Systematic Reviews-Meta Analysis) technique through four stages: identification, selection, eligibility, and inclusion. From 240 articles, seven national journal articles were selected as research data because they met the criteria determined by the researcher in the last five years. The literature review shows that interactive learning media such as Flashcards, Augmented Reality (AR), Interactive Multimedia, Articulate Storyline, Virtual Reality (VR), Science Monopoly, and Unity 3D can make abstract solar system material more concrete, thereby increasing students' enthusiasm, spirit, motivation to learn, and learning outcomes, as well as helping the right brain to remember concepts. The immersive, contextual, and enjoyable learning experience provided by learning media encourages deeper student engagement. The integration of appropriate learning media is essential to improve student learning outcomes, and the evaluation and updating of learning media must be carried out continuously to adapt to the characteristics of 21st-century students.